IMF Survey, Volume 35, Issue 11. (IMF Survey; IMF Survey, 2006)
Multilateral consultation; Euro Area; Caruana to head new Department; Marshall Islands; Malaysia; Inflation targeting; Offshoring U.S. services; Public sector credit; Singapore; Pakistan's inflation; Kyrgyz Republic; Latin America.